1984
DOI: 10.3109/03008208409013685
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tensional Load on Isolated Embryonic Chick Tendons in Organ Culture

Abstract: Digital flexor tendons isolated from 17-18 day embryonic chickens were cultured intact, either on steel mesh grids, or in an apparatus designed to apply a mechanical load to the tissue. Tendons cultured without an applied load continued to synthesize protein and glycosaminoglycans throughout a 7-day period, but DNA synthesis decreased during this time. Increases in both protein and DNA synthesis were observed in tendons experimentally loaded for 48-72 h. Glycosaminoglycan production by tendons isolated from 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
1
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 30 publications
2
29
1
1
Order By: Relevance
“…Similar increases were reported by Slack et al (1984), who found more synthetic activity of the matrix components in tendons of animals that performed intense physical activity.…”
Section: Discussionsupporting
confidence: 86%
“…Similar increases were reported by Slack et al (1984), who found more synthetic activity of the matrix components in tendons of animals that performed intense physical activity.…”
Section: Discussionsupporting
confidence: 86%
“…This stage constitutes a critical period of the development of the musculo-tendinous complex in which the muscle bellies become individualized (Pautou et al 1982) and contracting (see Watson and Bekoff 1990) and, as we showed in this study, the musculo-tendinous junction is established. Since mechanical tension has been proposed to stimulate elastic matrix synthesis (Slack et al 1984;Sutcliffe and Davison 1990;Keeley and Alatawi 1991) it is tempting to suggest a relationship between elastic matrix deposition in the tendons and the onset of their functional activity. Such a relationship is supported by the observation that the tendon blastemas in experimentally muscleless chick limbs undergo disintegration at the time when elastic matrix should be deposited (Kieny and Chevallier 1979).…”
Section: Extracellular Matrix Distributionmentioning
confidence: 99%
“…In contrast, mobilization of healing tendons in vivo affects the biomechanical and biochemical properties of flexor tendons (12). Applied tensional load on tendons cultured in serum-supplemented medium caused an increase in glycosaminoglycan and protein content (35) and of protein and collagen synthesis in aortic cells in culture (38). These reports together indicate that the metabolic state in a tendon is, besides hormonal factors, markedly influenced by the mechanical forces acting on the tendon.…”
mentioning
confidence: 99%